2005
DOI: 10.1002/poc.928
|View full text |Cite
|
Sign up to set email alerts
|

Steric and electronic substituent effects in hydrolysis and aminolysis of 4‐alkyl‐4‐methyl‐2‐aryl‐4,5‐dihydro‐1,3‐oxazol‐5‐ones

Abstract: The kinetics and mechanism of the acid-catalysed hydrolysis of substituted 4-alkyl-4-methyl-2-aryl-4,5-dihydro-1,3-oxazol-5-ones to the corresponding 2-alkyl-2-benzoylaminopropanoic acids were studied. The Taft correlation of rate constants of the acid-catalysed hydrolysis with alkyl substitution at the 4-position of the 1,3-oxazol-5-one ring is non-linear. In the Hammett correlation, the value of decreases with increasing steric demand of the alkyl substituent. With the 4-isopropyl and tert-butyl derivatives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The paper 60 was focused on study of kinetics and mechanism of acid-and base-catalysed hydrolysis of substituted 4-alkyl-2-aryl-4-methyl-4,5-dihydro-1,3-oxazol-5-ones to the corresponding 2-alkyl-2-benzoylaminopropanoic acids. The Taft correlation for acid-catalysed hydrolysis of 1,3-oxazol-5-one ring carrying various 4-alkyl substituents was not linear.…”
Section: Scheme 12mentioning
confidence: 99%
See 2 more Smart Citations
“…The paper 60 was focused on study of kinetics and mechanism of acid-and base-catalysed hydrolysis of substituted 4-alkyl-2-aryl-4-methyl-4,5-dihydro-1,3-oxazol-5-ones to the corresponding 2-alkyl-2-benzoylaminopropanoic acids. The Taft correlation for acid-catalysed hydrolysis of 1,3-oxazol-5-one ring carrying various 4-alkyl substituents was not linear.…”
Section: Scheme 12mentioning
confidence: 99%
“…The results of the above-mentioned study 60 provided a source of inspiration for an elegant synthesis of variously sterically hindered poly(ethylene glycol)carboxylic acids. These acids were prepared by the following reaction sequence (Scheme 13).…”
Section: Scheme 12mentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent transformation of terminal nitrile groups into carboxylic functional groups was carried out by using our earlier described synthesis and kinetic study of hydrolysis of substituted 4-alkyl-4-methyl-2-aryl-4,5-dihydro-1,3-oxazol-5-ones (azlactones). 13 In this case the hydrolysis of nitrile group proceeds with the assistance of neighboring amidic group as a sequence of a ring-closure reaction and hydrolysis. The ring closure producing the azlactone was performed in polyphosphoric acid.…”
mentioning
confidence: 99%
“…14 This method was adopted for preparation of 2-{4-[amethoxypoly(ethylene glycol)]oxybenzoylamino}-2,3-dimethylbutyric acid 15 (3a, 82%) and 2-(4-{a-[4-(1-carboxy-1-methylethylcarbamoyl)phenoxy]poly(ethylene glycol)-w-yloxy}benzoylamino)-2-methylpropionic acid 16 (3b, 89%). The course of transformation of nitrile group into carboxylic functional group was monitored by 13 C NMR spectroscopy, 17 which in the case of polymers 3a,b showed a signal at d = 174.7 ppm typical of the CO 2 H group, while the signal at d = 124.8 ppm typical of CN group (2a,b) completely disappeared. 15,16 Using GPC,18 it was demonstrated that the treatment with polyphosphoric acid did not cause any degradation of the poly(ethylene glycol) chain.…”
mentioning
confidence: 99%